Dampak Reformasi Kebijakan Perdagangan Luar Negeri Terhadap Kinerja Perdagangan Luar Negeri - Rahmasuciana, Dioni Yurinda; Rofii, Muhammad (Cendekia Niaga, 2024)
This study aims to identify Indonesia’s foreign trade policy reforms and analyze their impact on its foreign trade performance. This study focuses on the reforms of policy in foreign trade that includes the policies and regulations of both the export and the import sector after the Constitutions of Job Creation (UU Cipta Kerja) enforced. Descriptive and statistical analysis used in this study. Descriptive analysis is intended to identify any fundamental changes related to the regulations of foreign trade. Then, statistical analyses that consist of Paired T-Test and Correlations Test, are aim to capture the differences in the average of exports, imports, and trade balance value before and after the enactment of Minister of Trade Regulation Number 19 of 2021 concerning Export Policies and Regulations and the Minister of Trade Regulation Number 20 of 2021 concerning Import Policies and Regulation, and to find out the relationship between import and export activities. Based on descriptive analysis, the results show that fundamental changes occurred were the form of system changes, the simplification of licensing application requirements, and positive fictitious principles. Besides, based on the Paired T-Test, there is a difference between the average of export, import, and trade balance value before and after the Minister of Trade Regulations enforced. This indicates that the regulations have an impact on the value of exports, imports, and trade balance, which their value had increased after the implementation of the regulations. Furthermore, through correlation analysis, it is proven that the value of imports is positively correlated with the value of exports. So that, the value of imports is closely related to the increase of exports value. In other words, an increase in the value of imports followed by a higher increase in the value of exports, can increase the value of the trade balance.